2011
DOI: 10.5089/9781462311286.001
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Role for Funding in Explaining Recent U.S. Banks' Failures?

Abstract: This paper tests the role of different banks' liquidity funding structures in explaining the banks' failures, which occurred in the United States between 2007 and 2009. The results highlight that funding is indeed a significant factor in explaining banks' probability of default. By confirming the role of funding as the driver of banking crisis, the paper also recognizes that the new liquidity framework proposed by the Basel Committee on Banking Supervision appears to have the features to strenghten banks' liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…We develop a simple decision tree for assessing bank vulnerability that exploits information from only a small number of indicators via a sequence of binary, threshold rules. The performance of this tree is then compared with commonly used regression-based approaches that attempt to weight all the information optimally (BCBS, 2000;Ratnovski and Huang, 2009;Bologna, 2011;Vazquez and Federico, 2012). …”
Section: Simplicity Versus Complexity In the Prediction Of Bank Failurementioning
confidence: 99%
“…We develop a simple decision tree for assessing bank vulnerability that exploits information from only a small number of indicators via a sequence of binary, threshold rules. The performance of this tree is then compared with commonly used regression-based approaches that attempt to weight all the information optimally (BCBS, 2000;Ratnovski and Huang, 2009;Bologna, 2011;Vazquez and Federico, 2012). …”
Section: Simplicity Versus Complexity In the Prediction Of Bank Failurementioning
confidence: 99%
“…Banks with more stable funding structures continued to lend more relative to other banks during the global financial crisis (Cornett et al, 2010), and were less likely to fail (Bologna, 2011). The evidence also indicates that banks with larger capital cushions fared better during the global financial crisis in terms of stock returns (Demirgüç-Kunt and Huizinga, 2010).…”
Section: General Findings On the Performance And Risks Of Different Bmentioning
confidence: 61%
“…Short-term wholesale funding allows banks to manage their balance sheet size actively in a highly procyclical manner Shin 2010a, 2010b). In addition, banks with more stable funding structures continued to lend more relative to other banks during the global financial crisis (Cornett et al, 2010), and were less likely to fail (Bologna, 2011).…”
Section: Box 34: Literature Linking Bank Funding Models To Risksmentioning
confidence: 99%
“…230 In the same vein, the likelihood of failure among banks with less reliance on short-term wholesale funding was lower. 231 It is shown that universal banks have a greater reliance on short-term wholesale funding, have a higher average size, have greater volatility of earnings, and higher levels of market risk compared to other banking models. 232 On the other hand, the size and scope could not produce the claimed benefits, especially, the benefits of diversification were far limited than expected and it was far offset by additional complexity.…”
Section: Impact On Banking Business Models and Banking Stabilitymentioning
confidence: 99%